Sex differences in long QT syndrome - Díez-Escuté, Nuria; Arbelo, Elena; Martínez-Barrios, Estefanía; Cerralbo, Patricia; Cesar, Sergi; Cruzalegui, José; Chipa, Freddy; Fiol, Victoria; Zschaeck, Irene; Hernández, Clara; Campuzano, Oscar; Sarquella-Brugada, Georgia (Frontiers in Cardiovascular Medicine, 2023)
Long QT Syndrome (LQTS) is a rare, inherited channelopathy characterized by cardiac repolarization dysfunction, leading to a prolonged rate-corrected QT interval in patients who are at risk for malignant ventricular tachyarrhythmias, syncope, and even sudden cardiac death. A complex genetic origin, variable expressivity as well as incomplete penetrance make the diagnosis a clinical challenge. In the last 10 years, there has been a continuous improvement in diagnostic and personalized treatment options. Therefore, several factors such as sex, age diagnosis, QTc interval, and genetic background may contribute to risk stratification of patients, but it still currently remains as a main challenge in LQTS. It is widely accepted that sex is a risk factor itself for some arrhythmias. Female sex has been suggested as a risk factor in the development of malignant arrhythmias associated with LQTS. The existing differences between the sexes are only manifested after puberty, being the hormones the main inducers of arrhythmias. Despite the increased risk in females, no more than 10% of the available publications on LQTS include sex-related data concerning the risk of malignant arrhythmias in females. Therein, the relevance of our review data update concerning women and LQTS.